Study on intelligent response of emergency logistics under magnitude outburst public health events based on new generation information technology intelligent facilities and equipment - Li, Baozhu; Zhu, Tianyi; Gong, Weichen (2021 International Conference on E-Commerce and E-Management (ICECEM), 2021)
The concept of intelligent development of the logistics industry has been put forward to promote the deep integration of new generation information technology such as big data, block chain, 5G, artificial intelligence and its intelligent facilities and equipment with logistics activities. While in recent years, the outbreak of the COVID-19 has not only attracted worldwide attention, but also posed a challenge to the emergency logistics guarantee system throughout China in the process of epidemic prevention and control. In this paper, based on the existing research, the mechanism of material circulation under emergency is explored and improved based on blockchain with cryptography and smart contract technologies. After innovation and optimization, the mechanism makes it possible to improve the technology of emergency logistics and the level of deep application of wisdom, providing reasonable suggestions and improvement measures for the future management system.